Human Rights Implementation in The Means of Social Control on Lesbian Gay Biseksual Transgender (LGBT) In Indonesia - Desvia Winandra (Universitas Kuningan, 2018)
Human rights applied in Indonesia do not conflict with Pancasila, the 1945 Constitution and religion, and are relative-particularistic. All citizens have the basic rights to freedom. However, the freedom they possess has limits that apply to all citizens without exception, including for lesbian, gay, bisexual, and transgender (LGBT) people. The purpose of this research is to analyze the treatment and views of the society and the implementation of human rights on lesbian, gay, bisexual, and transgender. The method used was non-doctrinal research method. The results of the research showed that the presence of LGBT people is still accepted, but their behavior is not acceptable in society. In conclusion, human right is basically the basic right that every human being has from the womb, born until his death and this right is irrevocable for any reason, except by the Almighty God as the Creator. Indonesia strictly forbids LGBT because it is not in accordance with Pancasila and contradicts with Indonesian cultural values. Yet, in Human Rights Law context, LGBT should get the same rights as other citizens. Human Rights Law in Indonesia protects all citizens’ rights, without exception, especially their civil rights.Hak Asasi Manusia (HAM) yang berlaku di Indonesia tidak bertentangan dengan Pancasila, Undang Undang Dasar 1945 dan agama, serta bersifat partikularistik relatif. Semua manusia memiliki hak asasi atas kebebasan. Namun, kebebasan yang dimiliki memiliki batas-batas yang berlaku bagi semua orang tanpa terkecuali, termasuk bagi kaum lesbian, gay, biseksual, transgender (LGBT). Tujuan penelitian ini yaitu merumuskan perlakuan dan pandangan masyarakat serta implementasi hukum hak asasi manusia terhadap lesbian, gay, biseksual, transgender. Metode penelitain yaitu mengunakan penelitian non doktrinal. Hasil dari penelitian yang diperoleh menyatakan bahwa kaum LGBT kehadirannya masih diterima tetapi perilaku mereka tidak dapat diterima di dalam masyarakat. Simpulan yaitu bahwa Pada dasarnya hak asasi manusia merupakan hak dasar yang dimiliki setiap manusia sejak dalam kandungan, lahir sampai kematiannya yang tidak dapat dicabut dengan alasan apapun juga kecuali oleh Tuhan Yang Maha Esa sebagai penciptanya. Indonesia melarang keras LGBT karena tidak sesuai dengan Pancasila dan bersimpangan dengan nilai budaya Indonesia, tetapi dalam konteks Hukum Hak Asasi Manusia, LGBT seharusnya mendapatkan hak yang sama dengan masyarakat lain. Hukum Hak Asasi Manusia di Indonesia melindungi seluruh hak masyarakatnya, tanpa terkecuali, terutama hak sipilnya.